Regional Correlations in the Layered Deposits of Arabia Terra, Mars. Issue 6 (30th May 2020) - Annex, Andrew M.; Lewis, Kevin W.
Abstract: In the mid‐equatorial region of Arabia Terra, Mars, dozens of moderately sized impact craters (10 to 100 km diameter) contain layered sedimentary deposits. Previous work has found that these layers are resolvable at the meter scale and that they are quasiperiodic in expression. However, the interrelationships of these deposits, along with their formative depositional process, has not yet been determined. Proposed formation mechanisms include fluviolacustrine deposition, groundwater upwelling and evaporation, and aeolian or distal volcanic air fall. For this study, we measured layer thicknesses from stereo image‐derived topography within nine craters. We find two regionally extensive layered units with characteristic average bed thicknesses of 12 and 3.5 m and a possible third unit of intermediate thickness. Each unit was identified in a number of craters forming regionally consistent groups. These proposed units represent the first regional correlations of isolated sedimentary deposits in Arabia Terra and point to blanketing regional deposition over at least two separate geologic periods. Plain Language Summary: The Arabia Terra region of Mars contains layered rocks within craters that might have been formed by evaporated minerals or accumulated dust. We measured how thick the layers are within nine craters in Arabia Terra. We were able to correlate two different kinds of layered rocks based on how thick the layers were, either 12 or 3.5 m, across Arabia Terra. We think that these two regional units were formed by a single process that made similar layers over large areas, but likely during two different episodes. Key Points: We analyze bedding thicknesses within multiple intercrater sedimentary rock units Individual craters mostly have unimodal bed thickness, but there are sharp changes over short distances We identify two regionally extensive sedimentary units based on correlations in bed thicknesses